The framework of Portuguese intervention in humanitarian action - Pedroso, P. (Innovation in humanitarian response and participatory evaluation: Examples from Turkey, Columbia, Spain, Portugal, and Brazil: A handbook for professionals and academics, 2024)
This handbook explores innovative approaches to humanitarian action and participatory evaluation across five countries: Türkiye, Colombia, Brazil, Spain, and Portugal. It aims to bridge theory and practice by integrating academic insights with field experiences from NGOs and practitioners.